Analysis of the Colombian Medical Tourism Industry from a Systemic Competitiveness Approach (Dimensión Empresarial, 2018)
This research article analyzes the role of the central government of Colombia in the strategy for the improvement of the medical tourism industry through a critical approach of the traditional model of competitiveness. Based on a mixed method, the feasibility of the associative systemic competitiveness model and its effectiveness on the quality of medical services offered to foreign patients is determined. The proposal for the implementation of systemic competitiveness model improves the perception of quality of medical services by foreign patients. In order to implement the proposed model, it is recommended the expansion of free taxation zones, the proliferation of medical service clusters and the strengthening of strategic alliances with international operators.ResumenEste artículo de investigación analiza el papel del gobierno central de Colombia en la estrategia de posicionamiento del turismo médico a través de un enfoque crítico del modelo tradicional de competitividad. Con base en un método mixto, se determina la viabilidad del modelo asociativo de competitividad sistémica y su efectividad en la calidad de los servicios ofrecidos a pacientes extranjeros. La propuesta para la implementación del modelo de competitividad sistémica mejora la percepción de la calidad de los servicios médicos por parte de pacientes extranjeros. Para implementar el modelo propuesto, se recomienda la expansión de las zonas libres de impuestos, la proliferación de clústeres de servicios médicos y el fortalecimiento de alianzas estratégicas con operadores internacionales.ResumoEste artigo de pesquisa analisa o papel do governo central da Colômbia na estratégia para a melhoria da indústria do turismo médico através de uma abordagem crítica do modelo tradicional de competitividade. Com base em um método misto, determina-se a viabilidade do modelo associativo de competitividade sistêmica e sua efetividade na qualidade dos serviços médicos oferecidos a pacientes estrangeiros. A proposta de implementação do modelo de competitividade sistêmica melhora a percepção da qualidade dos serviços médicos por pacientes estrangeiros. Para implementar o modelo proposto, recomenda-se a expansão de zonas de tributação livre, a proliferação de clusters de serviços médicos e o fortalecimento de alianças estratégicas com operadores internacionais.
Keywords: Systemic competitiveness; Medical tourism; Government role; Traditional competitiveness model; Heath tourism